2019
DOI: 10.1177/0194599819881437
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Canal Occlusion for Intractable Posterior Canal Benign Paroxysmal Positional Vertigo: A Systematic Review

Abstract: Objectives A last resort for therapy for intractable benign paroxysmal positional vertigo (BPPV) is mechanical occlusion of the posterior semicircular canal. The aim of this review was to assess the effect of posterior canal occlusion for intractable posterior canal BPPV on vertigo and to determine the risk of loss of auditory or vestibular function. Data Sources A systematic literature search according to the PRISMA statement was performed on PubMed, the Cochrane Library, Embase, Web of Science, and CINAHL. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The present results emphasize the importance of a systematic follow-up to assess the impact of plugging of a semicircular canal on inner ear function. Systematic objective vestibular results are lacking and reported outcomes vary between studies [11,15,16,[18][19][20][26][27][28]. Mantokoudis et al evaluated three patients up to 1-4 months after plugging of the superior semicircular canal through a middle cranial fossa approach and showed recovery of lateral semicircular canal gain in 3/3 patients, while 1/3 showed recovery of posterior semicircular canal gain [15].…”
Section: Importance Of Timing Of Vestibular Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results emphasize the importance of a systematic follow-up to assess the impact of plugging of a semicircular canal on inner ear function. Systematic objective vestibular results are lacking and reported outcomes vary between studies [11,15,16,[18][19][20][26][27][28]. Mantokoudis et al evaluated three patients up to 1-4 months after plugging of the superior semicircular canal through a middle cranial fossa approach and showed recovery of lateral semicircular canal gain in 3/3 patients, while 1/3 showed recovery of posterior semicircular canal gain [15].…”
Section: Importance Of Timing Of Vestibular Testingmentioning
confidence: 99%
“…Previous studies have reported cases of transient hearing loss [12], persistent (high-frequency) sensorineural hearing loss [12][13][14], a decrease in vestibulo-ocular reflex (VOR) gain of all ipsilateral semicircular canals [15,16], or an increase in semicircular canal paresis, up to caloric areflexia [17][18][19]. Unfortunately, structured data on the occurrence of these side effects is lacking, especially regarding objective vestibular function [11,20]. Furthermore, since many studies use a single moment of postoperative evaluation and the follow-up interval differs between studies, assessment of the evolution of inner ear function over time is impeded [11,20].…”
Section: Introductionmentioning
confidence: 99%
“…Some surgeries have been performed in cases of intractable BPPV. In particular, canal plugging of the posterior canal has been reported [16,17]. This surgical effect depends on stopping ampullopetal and ampullofugal endolymph flow and its effect on the ampulla.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior canal plugging poses a substantial risk to hearing (3-20%), but success rate is about 85 to 90%. 12 Gacek proposed transaction of the posterior ampullary nerve for relief of BPPV. Most of the studies done earlier have compared the effectiveness of maneuvers but in this study, we compared the effectiveness of Cawthorne Cooksey exercise with Brandt Daroff exercise in patients with residual symptoms after successful Epley's maneuver.…”
Section: Introductionmentioning
confidence: 99%